História "histórica" da filosofia no Brasil: João Cruz Costa - Angelo Filomeno Palhares Leite (2014)
The study of João Cruz Costa career, from the late 1930´s to the 1950´s, rebuilding his intellectual background has shown how the cruzcostiano call on a historical history would lead him to the conclusion of the formation process of the philosophy history field in Brazil, which occurred with the advent of the historian work whose term was given by the publication of his book Contribuição à História das Ideias no Brasil: O desenvolvimento da filosofia no Brasil e a evolução histórica nacional (Contribution to the History of Ideas in Brazil: the development of philosophy in Brazil and a national historical evolution). The tradition revival, to which the author was bound, has shown how a number of notions and examples of attitudes of previous historians belonging to that tradition, who were appropriated and reinterpreted by Cruz Costa. Despite this aspect of conceptual and practical change, this active reference to the previous authors has characterized some continuity, even if it were to deny it, establishing a system according to Antônio Candidos understanding. The cruzcostiano time with his own mental variety and its practices was indicative of his historiographical conception, for when one thinks history and philosophy in close connection with each other, that expedient surfaced, providing the conditions for completion of the formation process in the philosophy history area in Brazil. The publication of the above mentioned book was the culmination of this journey. When one reads the book a very close relationship was verified, both between the present debates and the ones of his time, and the mentioned tradition to which his author was bound.